Harrison's manual of oncology (McGraw-Hill Medical, 2008)
From today's leading clinicians in cancer care comes this comprehensive yet portable guide to the major chemotherapeutic and supportive care agents in oncology. Full of never-before-published content, this invaluable clinical companion features numerous tables and a concise, outline-oriented text, making it ideal for reference at a glance